Do Immigrants Threaten US Public Safety?. (September 2019) - Orrenius, Pia; Zavodny, Madeline
Executive Summary: Opponents of immigration often claim that immigrants, particularly those who are unauthorized, are more likely than US natives to commit crimes and that they pose a threat to public safety. There is little evidence to support these claims. In fact, research overwhelmingly indicates that immigrants are less likely than similar US natives to commit violent and property crimes, and that areas with more immigrants have similar or lower rates of violent and property crimes than areas with fewer immigrants. There are relatively few studies specifically of criminal behavior among unauthorized immigrants, but the limited research suggests that these immigrants also have a lower propensity to commit crime than their native-born peers, although possibly a higher propensity than legal immigrants. Evidence about legalization programs is consistent with these findings, indicating that a legalization program reduces crime rates. Meanwhile, increased border enforcement, which reduces unauthorized immigrant inflows, has mixed effects on crime rates. A legalization program or other similar initiatives not currently under serious consideration have more potential to improve public safety and security than several other policies that have recently been proposed or implemented.